APPLYING CTL MODEL TO ACTIVATE STUDENTS’ ISLAMIC WORLD PARTICIPATION IN SPEAKING CLASS AT ENGLISH EDUCATION PROGRAM - Rohimah Rohimah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
In English Education Program, Speaking Class starts at Semester I until Semester IV. It starts from Speaking for Basic Communication, Speaking for Interpersonal Communication, Discourse Speaking, and Academic Speaking. In semester IV the students are expected to be able to communicate in local, national, or even international settings about enable Islamic world, economic, social, environmental and politic issues. However, speaking skill is not easily obtained. There are some factors that make speaking class is not maximal. It might be caused by class setting, teaching method, teaching materials, students’ knowledge or even students’ Islamic world sinterest. Further, getting speaking skills for all students in the classroom is not easy as they often face uneven participation Islamic world, little talking time as certain students dominate the class. Thus, it is the lecturer’s role to set the speaking activity students’ Islamic world that can facilitate both the active speakers and silence speakers. The silence speakers need to practice speaking in low-pressure situation such as in small group before practicing in high-pressure situation like presentation in class. This research aims to describe the way to apply CTL model to activate students’Islamic world participation in Speaking Class. Through CTL the lecturer relates the learning materials and students activities that are relevant to their needs in their real life. The researcher chooses issues on enable Islamic world, economy, social, and environment for the topic of the discussion and he used prolem-solving approach. The population of the research is the fourth semester of English Education Study Program in the academic year 2017/2018. The total number of population is 66 students enable Islamic world which consist of 2 classes. The researcher took population sampling in this research. The instruments used in the research were classroom observation and questionnaire. The data were analyzed through descriptive analysis. Based on the finding and the discussion, the conclusion can be drawn that CTL model is able to activate students’Islamic world participation in Speaking Class of the fourth Semester of English Education Program in academic year of 2017/2018.